Social capital dimensions and individual happiness in Indonesia: The micro-level study - Mimi Hardini; Wasiaturrahma Wasiaturrahma (Jurnal Ekonomi Pembangunan, 2020)
The Easterlin Paradox triggers the use of happiness as a measure of Wellbeing. The welfare can be measured by monetary measurement and comprehensive to subjective measurement, one of which is social capital. This study shows the influence of social capital on the level of individual happiness in Indonesia. The study uses the 2007 and 2014 Indonesia Family Life Survey (IFLS) data. Using the Logit Regression Panel, the results show a positive influence on social capital, which contains trust, social networks, and sanctions and norms on several dimensions on the level of individual happiness. We also found that individual happiness levels are based on age, marital status, income level, education level, health status. Therefore, we need programs that prioritize community participation to increase informal social interaction and the need for effective programs to accelerate community income.